EFFECTIVENESS OF E-LEARNING MEDIA DEVELOPMENT USING CANVA IN THE PJBL MODEL - Taukhid Taukhid; Taufan Agung Prasetya; Sapto Dwi Anggoro (STKIP PGRI Tulungagung, 2025)
The purpose of this research is to develop Canva-based learning media using the Project-Based Learning model in Pancasila Education at STIKES Hang Tuah Surabaya that is valid and practical. The method used in this research and development is the ADDIE model. Data were obtained from validation questionnaires and practicality question-naires. The research subjects consisted of 3 expert validators covering media, language, and content, while peer testing involved 1 person, and 23 nursing students from STIKES Hang Tuah Surabaya. The results of the media development research showed that the content validity level was 90 percent categorized as very valid, language validity was 95 per-cent categorized as very valid, and media validity was 98 percent cate-gorized as very valid. Furthermore, the practicality response from stu-dents was 89.31 percent categorized as very practical, while the feed-back from educators showed 91.66 percent categorized as very practi-cal. The results of the study found that the Canva-based learning media using the Problem-Based Learning model is very valid and practical for use in Pancasila education for nursing students at STIKES Hang Tuah Surabaya.